Population Density of Plant-parasitic Nematodes Associated with Some Forest Trees in Orissa - Raman, S.; Das, S. N. (Indian Forester, 1980)
Occurrence of ten types of plant parasitic nematodes was noticed around the root zones of 26 different forest trees in the Khurdha and Nayagarh forest ranges of Orissa. The relative abundance of the important nematode species in the descending order is as follows: Xiphinema, Hemicycliophora, Hoplolaimus, Paralongidours, and Longidorus: maximum number of which were recorded on Tectona grandis L., Emblica officinalis Gaertn, Casiaroms equisetifolia Forst. Syzygium cuminii Skeel., Shorea robusta Gtn., respectively. Among these plants, S. cuminii was found to be the most favoured host for the nematodes and no parasitic forms were obtained from the rhizospheres of Ficus carica L. and Pinus roxburghii Sargent.